2015
DOI: 10.1007/s00359-015-1037-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and rate code analysis of responses to low-frequency components in the bird’s own song by song system neurons

Abstract: Auditory feedback (AF) plays a critical role in vocal learning. Previous studies in songbirds suggest that low-frequency (< ~1 kHz) components may be salient cues in AF. We explored this with auditory stimuli including the bird’s own song (BOS) and BOS variants with increased relative power at low frequencies (LBOS). We recorded single units from BOS-selective neurons in two forebrain nuclei (HVC and Area X) in anesthetized zebra finches. Song-evoked responses were analyzed based on both rate (spike counts) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Besides firing rates, the temporal pattern of spike timings also carries important information about brain functions. For instance, it has been shown that temporal patterns encode the information of auditory (Machens et al, 2001;Narayan et al, 2006;Wang et al, 2007;Fukushima et al, 2015;Krause et al, 2017), gustatory (Di Lorenzo and Victor, 2003), motor (Vargas-Irwin et al, 2015), olfactory (MacLeod et al, 1998), somatosensory (Harvey et al, 2013), vestibular (Jamali et al, 2016), and visual (Mechler et al, 1998;Victor and Purpura, 1998;Reich et al, 2001;Carrillo-Reid et al, 2015) systems, as well as behavioral adaptation (Logiaco et al, 2015) and sleep (Tabuchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides firing rates, the temporal pattern of spike timings also carries important information about brain functions. For instance, it has been shown that temporal patterns encode the information of auditory (Machens et al, 2001;Narayan et al, 2006;Wang et al, 2007;Fukushima et al, 2015;Krause et al, 2017), gustatory (Di Lorenzo and Victor, 2003), motor (Vargas-Irwin et al, 2015), olfactory (MacLeod et al, 1998), somatosensory (Harvey et al, 2013), vestibular (Jamali et al, 2016), and visual (Mechler et al, 1998;Victor and Purpura, 1998;Reich et al, 2001;Carrillo-Reid et al, 2015) systems, as well as behavioral adaptation (Logiaco et al, 2015) and sleep (Tabuchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, by removing rate dependence from the SPIKEdistance, Satuvuori et al (2017) proposed the RI-SPIKE-distance as a distance purely sensitive to timing. The spike train distances developed so far have been used in a number of studies for the analysis of neural firing patterns (MacLeod et al, 1998;Mechler et al, 1998;Victor and Purpura, 1998;Machens et al, 2001;Reich et al, 2001; Di Lorenzo and Victor, 2003;Narayan et al, 2006;Wang et al, 2007;Harvey et al, 2013;Fukushima et al, 2015;Logiaco et al, 2015;Vargas-Irwin et al, 2015;Jamali et al, 2016;Krause et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is done under the underlying assumptions that the rate is the most important feature of the response, that the number and density of spikes is high enough to estimate it reliably and, crucially, that the timing of the individual spikes can be neglected. These assumptions hold for a wide variety of real data ( Walter and Khodakhah, 2009 , Enoka and Duchateau, 2017 ) but there are also many datasets in which this is not the case ( van Rullen and Thorpe, 2001 , Harvey et al, 2013 , Fukushima et al, 2015 ) and for which so far no reliable and feasible method of latency correction has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…This is done under the underlying assumptions that the rate is the most important feature of the response, that the number and density of spikes is high enough to estimate it reliably and, crucially, that the timing of the individual spikes can be neglected. These assumptions hold for a wide variety of real data [19,20] but there are also many datasets in which this is not the case [21,22,23] and for which so far no reliable and feasible method of latency correction has been proposed. Therefore, here we would like to address the complementary problem of latency correction in data in which there are not that many spikes and where the relevant information is not primarily in the rate but in the timing of each individual spike.…”
Section: Introductionmentioning
confidence: 99%